2010
DOI: 10.1038/nsmb.1878
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pore formation but not nuclear growth is governed by cyclin-dependent kinases (Cdks) during interphase

Abstract: Nuclear volume and the number of nuclear pore complexes (NPCs) on the nucleus almost double during interphase in dividing cells. How these events are coordinated with the cell cycle is poorly understood, particularly in mammalian cells. We report here, based on newly developed techniques for visualizing NPC formation, that cyclin-dependent kinases (Cdks), especially Cdk1 and Cdk2, promote interphase NPC formation in human dividing cells. Cdks seem to drive an early step of NPC formation because Cdk inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
105
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 47 publications
14
105
0
1
Order By: Relevance
“…[3][4][5][6][7] To address this question, we established novel techniques to study nuclear volume and NPC formation, and investigated how they were regulated during interphase in dividing human cells. 8,9 Our results indicate that Cdks, especially Cdk1 and Cdk2, control NPC formation during interphase. 9 Cdk inhibition suppressed the generation of the "nascent pores," which are immature NPCs in the process of forming and interrupted expression and localization of some nucleoporins.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…[3][4][5][6][7] To address this question, we established novel techniques to study nuclear volume and NPC formation, and investigated how they were regulated during interphase in dividing human cells. 8,9 Our results indicate that Cdks, especially Cdk1 and Cdk2, control NPC formation during interphase. 9 Cdk inhibition suppressed the generation of the "nascent pores," which are immature NPCs in the process of forming and interrupted expression and localization of some nucleoporins.…”
Section: Introductionmentioning
confidence: 80%
“…8,9 Our results indicate that Cdks, especially Cdk1 and Cdk2, control NPC formation during interphase. 9 Cdk inhibition suppressed the generation of the "nascent pores," which are immature NPCs in the process of forming and interrupted expression and localization of some nucleoporins. Surprisingly, we also demonstrated that Cdk inhibition did 10 When we used Nup62-YFPexpressing cells, the NPC acceptor nuclei acquired Nup62-YFP signals without interphase NPC formation, likely due to the rapid turnover of Nup62-YFP within NPCs (Maeshima K, et al unpublished).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…(15) to a distribution function f i (r) if r was located in the segmented nucleus (cytoplasm) and an adjacent point r + δrê i was located on the other side of the membrane in the segmented cytoplasm (nucleus). The permeability of the envelope was assumed to be uniform, since the density of the nuclear pores is high and they are rather uniformly located over the nuclear envelope [27,28]. Furthermore, the permeability was assumed to be constant during the simulation, since the total simulated time (only a few seconds) was short.…”
Section: B Simulation Setupmentioning
confidence: 99%
“…Using the solubility-diffusion model (see Introduction), P = KD m /w, together with equation A pore = K/n, where A pore is the cross-sectional area of one nuclear pore channel and n is the area density of the nuclear pores, we calculated a rough estimate for the effective nuclear pore diameter. The value D m that we used was the average of the nucleus and cytoplasm diffusion coefficients that we determined (21 μm 2 /s) and the value of n was the average of values from [27,28] (25 μm −2 ) and w ∼ 65 nm [29,30]. This way we obtained the effective nuclear pore area A pore ∼ 62 nm 2 , or effective pore diameter d pore ∼ 8.9 nm, which is in good agreement with experimental data [31,32].…”
Section: Determination Of the Nuclear Permeability Of Eyfpmentioning
confidence: 99%